Paul Baudoüin, Georges Pradelle et l’association « la Fresque » - Marie Monfort (In Situ)
Paul Baudoüin (1844-1931) played a very important part in the revival in fresco painting in the beginning of the twentieth century. In 1888, he began to experiment painting in fresco. He published in 1914 : « La Fresque, sa technique et ses applications ». This book summarizes twenty years or research and work. Baudoüin became a professor at the Ecole Nationale des Beaux-Arts, from 1919 to 1929. To allow his students to paint on walls and to work, the painter funded with Georges Pradelle a society of painters in fresco : “La fresque”. Established in a school belonging to the city of Paris, rue de la Villeneuve, the students painted temporary frescoes, soon destroyed to be replaced. The members participated also in numerous works of paintings in fresco in different buildings.